Quarter-century anniversary of the Russian Constitution - A. Kostyukov (Правоприменение, 2018)
The subject of the paper is the constitutional development of Russia till 1990s up to 2018.The purpose of the paper is to identify the main trends in development of Russian consti-tutional legislation.The methodology of the research includes the formal legal analysis of Russian federal laws and their comparison with the decisions of Russian Constitutional Court.The main results and scope of their application. The author gives the legal assessment to main novelties in Russian constitutional legislation: an increase of the term of office of the President of the Russian Federation and the State Duma of the Russian Federation, the in-troduction of the annual reports by the Government of the Russian Federation to the State Duma of the Russian Federation on the results of their activities, the merger of the Supreme and Supreme Arbitration Courts of the Russian Federation, the strengthening of the posi-tions of the President of the Russian Federation when appointing prosecutors, judges, members of the Federation Council, officials of subjects of the Russian Federation, central-ization of local self-government. The identified trends may be used in future research of Russian constitutional legal order.The author comes to the conclusion that there is a need for strong state power in the con-ditions of reforming economic, social and state-legal institutions in Russia. The movement towards centralization and strengthening of the power vertical is a historically necessary and justified measure. It will be possible to implement decentralization and reduction of the regulatory functions of the state after the successful modernization of economic and social state and legal institutions.